2015
DOI: 10.1108/nfs-04-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological contamination sources of freshly cultivated vegetables

Abstract: Purpose – The purpose of the paper is to emphasize on contamination sources of freshly cultivated vegetables commonly consumed by the Bangladeshi people. Several local studies have been conducted to detect the microbial contamination within fresh vegetables, plantation lands and the irrigation waters separately; however, the correlation of microbial contamination between the fresh produces and the surrounding environment has not been clarified. Design/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…In Bangladesh, such microbial growth simulating research on fresh vegetables is still in its infancy and data are scanty except a few reports (Rahman and Noor 2012;Fatema et al 2013;Ahmed et al 2014;Senjuti et al 2014;Tahera et al 2014;Alam et al 2015). However, in the current study we have further extended our research on the bacterial survival within capsicum, chili, coriander and onion samples.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In Bangladesh, such microbial growth simulating research on fresh vegetables is still in its infancy and data are scanty except a few reports (Rahman and Noor 2012;Fatema et al 2013;Ahmed et al 2014;Senjuti et al 2014;Tahera et al 2014;Alam et al 2015). However, in the current study we have further extended our research on the bacterial survival within capsicum, chili, coriander and onion samples.…”
Section: Introductionmentioning
confidence: 82%
“…Previously we found the fresh vegetables to be contaminated by an array of microorganisms, of which most were resistant against the commonly used antibiotics (Rahman and Noor 2012;Ahmed et al 2014;Alam et al 2015;Noor and Feroz 2015). Conversely, an antibacterial activity of lettuce and cucumber samples against potential pathogenic bacteria was also notable (Ahmed et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…globe, Bangladeshi people are more likely to be prone to microbial attack due to the relatively dense population with extremely unhygienic sanitary facilities (11,31,32). Several researches revealed that the propagation of waterborne microorganisms into the environment causing cholera and diarrhoea is very frequent in this country (32)(33)(34). A recent estimation has revealed that approximately 30 million people in Bangladesh suffer from foodborne illnesses each year (8,35).…”
Section: Microbiological State Of Common Foods In Bangladeshmentioning
confidence: 99%
“…In principle, the microbial load of plants is the result of a series of influences caused by animate & inanimate sources and microbial contaminates are easily transferred via air and soil borne vectors (20)(21)(22)(23). Furthermore, original microflora in plants, presence of microorganisms within processing plant, dust, using contaminated water and animal human a excreta, before and after harvest procedure including processing, storage and distribution may be the origins of microbial contamination (20,24). In addition, the collection and handling of medicinal plants does not usually done in sanitary conditions and unhygienic cultivation conditions can increase pollution, influence the maintenance period and destruct the aspect and the potential advantage of medicinal plants (9,25).…”
mentioning
confidence: 99%